Effects of interparticle attractions on colloidal sedimentation. - Moncho-Jordá, A; Louis, A; Padding, J (2010)
We use a mesoscopic simulation technique to study the effect of short-ranged interparticle attractions on the steady-state sedimentation of colloidal suspensions. Attractions increase the average sedimentation velocity v(s) compared to the pure hard-sphere case, and for strong enough attractions, a nonmonotonic dependence on the packing fraction phi with a maximum velocity at intermediate phi is observed. Attractions also strongly enhance hydrodynamic velocity fluctuations, which show a pronounced maximum size as a function of phi. These phenomena arise from a complex interplay between nonequilibrium hydrodynamic effects and the thermodynamics of transient cluster formation.